2014
DOI: 10.1002/cmdc.201402353
|View full text |Cite
|
Sign up to set email alerts
|

Conjugation of Cisplatin Analogues and Cyclooxygenase Inhibitors to Overcome Cisplatin Resistance

Abstract: Cyclooxygenase (COX) is an enzyme involved in tumorigenesis and is associated with tumor cell resistance against platinum-based antitumor drugs. Cisplatin analogues were conjugated with COX inhibitors (indomethacin, ibuprofen) to study the synergistic effects that were previously observed in combination treatments. The conjugates ensure concerted transport of both drugs into cells, and subsequent intracellular cleavage enables a dual-action mode. Whereas the platinum(II) complexes showed cytotoxicities similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(70 citation statements)
references
References 97 publications
1
68
0
Order By: Relevance
“…For this scope, we decided to study the complexes alone or conjugated to the nonsteroidal anti‐inflammatory drug (NSAID) indomethacin. This chemical design was inspired by the fact that molecular units comprising a metal fragment and NSAID have been previously reported to enhance anticancer properties . Remarkably, it was found that the rhenium complexes were active against pancreatic cell lines, whereas the ruthenium complexes did not show any significant activity.…”
Section: Figurementioning
confidence: 86%
See 1 more Smart Citation
“…For this scope, we decided to study the complexes alone or conjugated to the nonsteroidal anti‐inflammatory drug (NSAID) indomethacin. This chemical design was inspired by the fact that molecular units comprising a metal fragment and NSAID have been previously reported to enhance anticancer properties . Remarkably, it was found that the rhenium complexes were active against pancreatic cell lines, whereas the ruthenium complexes did not show any significant activity.…”
Section: Figurementioning
confidence: 86%
“…This chemicald esign wasi nspired by the fact that molecular units comprising am etal fragment and NSAID have been previously reported to enhancea nticancerp roperties. [20][21][22][23][24][25][26] Remarkably,i t was found that the rhenium complexes were active against pancreatic cell lines, whereas the ruthenium complexes did not show any significant activity.F urthermore,c onjugation to indomethacin did not seem to enhancet he anticancer activity, which was traced back exclusively to the presence of the Re(CO) 3 fragment. With this study,f or the first time, it was possible to elucidate that the anticancer properties of the rhenium tricarbonyl fragment originatef rom the labilityo ft he monodentate ancillary ligand coordinated to the rheniumc enter by inducing G2/M cell cyclea rrest and blockade of Aurora-A kinase phosphorylation.…”
mentioning
confidence: 99%
“…Specifically, the conjugation with cyclooxygenase inhibitors was reported to facilitate the cellular accumulation of Pt(IV) complexes and to overcome cisplatin resistance [49]. In the reported conjugates (24) the COX-2 inhibitor served as axial ligand, allowing the release of platinum complex and of two molecules of the COX-2 inhibitor following intracellular thio-mediated reduction.…”
Section: Bifunctional Agents With Cleavable Linkersmentioning
confidence: 99%
“…73 In this regard, Hey-Hawkins and coworkers also reported covalently linked conjugates of cisplatin and cyclooxegenase COX inhibitors which demonstrated similar mechanism of action after intracellular cleavage of the components (Figure 4A). 74 They used indomethacin or ibuprofen as the axial ligands. Preliminary studies could not decipher the precise reasons for improved cytotoxicity and increased lipophilicity of the overall molecules leading to greater cellular uptake was thought to be the predominating factor.…”
Section: Activationmentioning
confidence: 99%